Physiological quality of citrandarins, Poncirus trifoliata and Sunki mandarin seeds - da Conceição, Patrícia Marluci; de Azevedo, Fernando Alves; Ecker, Gerhard Vitor; Morelli, Marilia; Cristofani-Yaly, Mariangela (Comunicata Scientiae, 2019)
Rangpur lime is the rootstock most used in Brazil, mainly due to its resistance to drought; however, it is susceptible to several diseases, requiring the search for other rootstocks tolerant to factors limiting citrus cultivation. In addition, the Brazilian legislation stipulates that citrus seeds can only be commercialized with at least 50% germination rate. Thus, the aim of this work was to evaluate the physiological quality of seeds of seven citrus rootstocks. The following citrus fruits were harvested: Poncirus trifoliata, Sunki mandarin and their hybrids –citrandarins (70, 106, 254, 299 and 310). Fruit mass, diameter and height were measured. Seeds were extracted from fruits, counting the number of normal seeds (not aborted). Seeds were dried up to 20% water content and stored for 3, 6, 9 and 12 months. The physiological quality of seeds was evaluated before storage (time 0) up to 12 months of storage. The quality of Poncirus trifoliata, Sunki mandarin and citrandarins 70, 106, 254, 299 and 310 seeds was reduced during storage. However, their germination rate remained above 50%, evidencing that seeds of all rootstocks could be marketed until 12 months of storage. The new rootstocks tested have seeds with physiological quality compatible with their parents, in compliance with current legislation.